A Qualitative Study of the Mobile Application Concept Among T2D Patients - Kurnia, Anih; Said, Farida Mohd; Paduragan, Santhna Letchmi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Self-care is the most fundamental and vital component of diabetes management. It necessitates patient participation in disease management activities such as nutrition, physical activity, medication adherence, and foot care procedures. However, developments in smartphone technology have created new options for diabetes self-management and diabetes education. The purpose of this study is to gain an overview of the mobile application concept that is expected among T2D patients in order to build application-based therapies based on the research site. This research method employs qualitative approaches in conjunction with a grounded theory approach. The approach employed is the sampling quota selection method. A Focus Group Discussion (FGD) was held with all qualified participants. A grounded theory technique was used to analyze the data. The findings of the study highlighted six themes: 1) Diet, 2) psychological activity, 3) medication alarms, 4) blood glucose monitoring, and 5) reduced worry (knowledge about health problems), 6) Consulting with health-care providers and asking questions. Self-care management can improve the quality of life of T2D patients. Diabetes patients in Indonesia are treated in a variety of ways; a link between patient experience, care, and health support is required.